Os impactos socioeconômicos da prática de atividades físicas no Brasil: uma análise sobre renda e defasagem idade-série. - Davinha, Ana Helena Nallin (Universidade Federal de São Carlos, 2020)
The practice of physical activities has become a source of ample debates both in the academic environment and in the daily life of individuals, with respect to their benefits to physical and mental health. Despite this, little has been discussed in these two spheres regarding the socioeconomic impacts of physical activity practice. Therefore, the main objective of this study is to analyze the practice of physical activities as an economic problem, insofar as it affects the health and quality of life (well-being) of individuals, consequently causing impacts on their productivity and ability to earn income. For adults (those between 18 and 65 years old), we analysed the relationship between physical activity practice and individual income earning. As for school-aged individuals (adolescents, aged 15 to 17 years old), as physical activity, besides being included in the school hours, also impacts their physical and metal well-being, we analysed the impacts of the practice of physical activities on the academic performance of adolescents, that is, on their age-grade gap. In order to do so, the statistical-econometric methodology was used as a way of analyzing and evaluating these relations, using the Heckman equation for income and count data models for the age-grade gap. The results on income show that physical activity practice (PAP) not only can lead to positive impacts on the individuals' health stock, but can also affect their income earnings, becoming a socioeconomic issue that affects the quality of life of individuals through many means. Thus, we find that the practice of any kind of physical activity out of the work hours increases the individual’s income earnings by 10.2% (IV-Probit IV-GMM) to 12.3% (BP IV-GMM), on average. This result was obtained while controlling the estimations for selection bias and for the presence of endogeneity between PAP and the individual's occupational situation and income. These PAP impacts vary across sexes and throughout age groups, so that PAP displays greater impacts on men’s income earnings, and an inverted U-shaped behavior across age groups, similar to the very impacts of age and experience on income (MINCER, 1958; SCHULTZ, 1961). As for the age-grade gap, the effects of PAP on the academic performance of adolescents were quite different for boys and girls: while, for the girls, the fact of participating on out-of-school hours PAP reduces their age-grade gap by 24.8%, or 0.281 years (around 3.4 months), on average, for the boys, the PAP was, in most cases, statistically zero in terms of affecting AGG. Even more, considering exclusively those boys regularly attending school, the NBRM MEs point out to a positive effect of participating on PAP on their age-grade gap, so that it negatively affects the academic performance of these boys.
The socioeconomic impacts of physical activities practice in Brazil: an analysis over income and age-grade gap.
Keywords: Saúde e Desigualdade; Bem-Estar; Diferenciais Salariais; Seleção Amostral; Variáveis Instrumentais; Health and Inequality; Welfare; Wage Differentials; Sample Selection; Instrumental Variables; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DOS RECURSOS HUMANOS::MERCADO DE TRABALHO; POLITICA DO GOVERNO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA